1994
DOI: 10.1007/bf01371096
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes and mating types of clinical strains ofCryptococcus neoformans isolated in Taiwan

Abstract: Twenty-one strains of Cryptococcus neoformans isolated from patients in Taiwan were characterized for serotypes and mating types. Slide agglutination test was performed with 8 factor-specific sera (Iatron Company, Japan) to determine the serotypes. Wheat bran agar (WBA) and malt extract agar (MEA, Wickerham) media were used for the mating tests. Twenty of the isolates were of serotype A, and one was serotype B. Except for 2 strains of serotype A, all of the serotype A strains mated with Filobasidiella neoforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…There have been many reports on the varying of occurrence of C. neoformans in avian droppings (Hsu et al, 1994;Khorsavi et al, 1997;Kielstein et al, 2000;Yimtubezenash et al, 2001). In this study, all isolates were obtained from pigeon droppings, demonstrating that pigeon dropping is the prinicipal environmental sources for C. neoformans in Korea.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been many reports on the varying of occurrence of C. neoformans in avian droppings (Hsu et al, 1994;Khorsavi et al, 1997;Kielstein et al, 2000;Yimtubezenash et al, 2001). In this study, all isolates were obtained from pigeon droppings, demonstrating that pigeon dropping is the prinicipal environmental sources for C. neoformans in Korea.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies covering more wide areas with high number of samples will be needed to examine the population structure of C. neoformans in Korea. In other east Asian countries such as Japan and Taiwan, only serotype A was reported from clinical samples (Hsu et al, 1994;Kohno et al, 1994). Serotyping of Korean clinical samples was not reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…are rare. [22][23][24] We previously reported that environmental C. gattii s.l. strains are representative of clinical strains.…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, existen evidencias importantes que establecen una relaci贸n entre la distribuci贸n mundial de C. neoformans y los suelos contaminados con excretas de aves (Hsu et al, 1994;Emmons, 1995;L贸pez-Mart铆nez & Casta帽贸n-Olivares, 1995;Passoni, 1999;Chee & Lee, 2005;Curo et al, 2005;Gonz谩lez Acu帽a et al, 2007). Esta peculiar distribuci贸n geogr谩fica hace importante el estudio de su nicho ecol贸gico, como posible fuente de contagio para individuos susceptibles (Staib, 1987).…”
Section: Introductionunclassified